Underactuated Control of Multi-Port Systems with Fuel Cells Using Nonlinear Control - Valdivia-Lefort, P (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper addresses the challenge of efficiently integrating fuel cells into multi-port energy systems, presenting an innovative underactuated nonlinear control strategy that eliminates the need for a DC-DC converter, thereby, enhancing system efficiency. By directly connecting the fuel cell to the DC bus and employing a supercapacitor as an auxiliary power source, the proposed nonlinear control technique effectively regulates the operation of both energy sources. The system s architecture is designed to adjust the operating points of the fuel cell and supercapacitor through indirect voltage regulation, which is achieved by manipulating the DC-DC converter linked to the supercapacitor. This allows the system to adapt dynamically to varying load demands without the energy losses typically associated with conventional converters. Simulation and experimental results confirm the viability of the proposed method in a case study on an energy storage system with fuel cells, demonstrating its potential to improve the responsiveness and efficiency of fuel cell-based systems, particularly in applications requiring rapid power adjustments such as electric vehicles and renewable energy integrations. The findings contribute to the ongoing efforts to optimize hybrid energy systems, highlighting significant advancements in control strategies and system design. © 2024 IEEE.